Optimal Human Embryo Culture - Swain, Jason E. (Seminars in Reproductive Medicine, 2015)
A large contributor to success during in vitro fertilization (IVF) lies in the processes occurring within the IVF laboratory. These processes make up the “culture system.” This system entails numerous procedures and technical steps that must be optimized to produce a competent embryo. Notably, variations exist between programs that include differences in patient population, clinical stimulation, and other factors. Thus, a single “optimal” culture system to be utilized between all laboratories is likely not feasible. Rather, laboratory procedures should be optimized based on an individual laboratory's performance. That being said, within the scientific literature, there are key components, approaches, and techniques within the culture system that have been shown to be superior to alternatives. These key components important in improving embryo culture are discussed.
Keywords: optimal; culture; embryo; blastocyst; IVF